Stolen Harvest : The Hijacking of the Global Food Supply - Shiva, Vandana (Culture of the land., 2016)
For the farmer, the seed is not merely the source of future plants and food; it is a vehicle through which culture and history can be preserved and spread to future generations. For centuries, farmers have evolved crops and produced an incredible diversity of plants that provide life-sustaining nutrition. In India alone, the ingenuity of farmers has produced over 200,000 varieties of rice, many of which now line store shelves around the world. This productive tradition, however, is under attack as globalized, corporate regimes increasingly exploit intellectual property laws to annex these sustaining seeds and remove them from the public sphere. In Stolen Harvest: The Hijacking of the Global Food Supply, Shiva explores the devastating effects of commercial agriculture and genetic engineering on the food we eat, the farmers who grow it, and the soil that sustains it. This prescient critique and call to action covers some of the most pressing topics of this ongoing dialogue, from the destruction of local food cultures and the privatization of plant life, to unsustainable industrial fish farming and safety concerns about corporately engineered foods. The preeminent agricultural activist and scientist of a generation, Shiva implores the farmers and consumers of the world to make a united stand against the genetically modified crops and untenable farming practices that endanger the seeds and plants that give us life.